Alginate Characteristics and Fucoxanthin Content from Sargassum polycystum Through Ultrasound-Assisted Extraction and the Relationship with Water Quality of Habitat - Nurbani, Siti Zachro; Sumandiarsa, I Ketut; Hidayah, Laely Nur; Siregar, Rezky Yunitasari (Polish Journal of Natural Sciences, 2023)
The study attempted to obtain alginate and fucoxanthin from Sargassum polycystum C. Agardh using ultrasound-assisted extraction (UAE) and to correlate these with the water’s environmental condition. The alginate was extracted using an acid pathway, the fucoxanthin was quantified using high-performance liquid chromatography, and the trace element was obtained using an atomic absorption spectrophotometer (AAS). The nutrients and micronutrient composition of S. polycystum were dominated by carbohydrates (32.8; 1.6%), with the main trace elements being selenium, iron, copper, and zinc. The alginate was attributed to 8.98±0.1 pH, 12.55±0.5% of water content, 22.63±0.9% of ash content, 70.28±0.5 Cps. of viscosity, and 37.24±0.8% of yield. The extract was also containing fucoxanthin, which was relatively high (0.41–0.59 mg g-1). There was a favourable association between water quality and the content of alginate, fucoxanthin, and nutrition. According to the ultrasonication extraction process, S. polycystum could produce high-quality alginate with a high fucoxanthin content.